Sexual activity and behavior of women with precancerous lesions of the vulva - Dunaevskaya, V. (Journal of Education, Health and Sport, 2024)
The aim of the study was to study the characteristics of sexual relations and sexual behavior of healthy women and women with precancerous lesions of the vulva. Materials and methods. In total, 258 women with lesions of the vulva aged from 25 to 70 years and 60 gynecologically healthy women (30 under the age of 50 and 30 after 50 years) were included in the study. Patients with precancerous lesions were divided into 4 groups: 87 women with high-grade intraepithelial neoplasia of the vulva (VHSIL) (Group 1 - G1), 154 - with differentiated vulvar intraepithelial neoplasia (dVIN) (Group 2 - G2), 9 - with Paget’s disease (Group 3 – G3), 8 - melanoma in situ of the vulvar skin (Group 4 - G4). Healthy women were divided into groups CG1 and CG2 according to age <50 years and ≥ 50 years. Sexual activity and behavior were assessed. Results. According to the obtained data, the interviewed women did not differ significantly in age at the start of sexual life, but the average number of sexual partners in patients with VHSIL (6.10±0.26) exceeded that of women with dVIN (3.71±0.15) by 1, 64 times (p<0.01), with Paget’s disease of the vulva (2.56±0.70) - 2.38 times (p<0.01), with melanoma in situ (3.80±0.62) – 1.61 times (p<0.01), CG1 (1.20±0.09) – 5.08 times (p<0.01). When assessing the frequency of sexual activity, it was found that at the time of the survey, 1 (1.15%) women of group G1, 45 (29.22%) of group G2, 2 (22.22%) of group G3 and 1 (12,50%) of group G4. All women of the CG1 group indicated the presence of sexual relations, and only 4 (13.33%) women of the CG2 group did not have sexual relations. Conclusions. The conducted study showed that compared to healthy women, women with precancerous lesions of the vulva have an increased total number of sexual partners and a reduced frequency of current sexual activity, vaginal sex, and satisfaction with sexual activity.